Reflections on the reconciliation problem - Ondřej Lopušník (Charles University in Prague, Institute of Economic Studies (IES), 2011)
This paper deals with the so called problem of reconciliation, a contentious and puzzling issue in Post Keynesian monetary theory. The crux of the matter is the question of mechanisms that would reconcile the loan-created supply of deposits with the willingness of agents to hold these deposits. The paper reviews and comments on the solutions proposed so far and argues that the reconciliation problem might not be eliminated entirely. The argument is twofold. First, it is argued that the income multiplier and Kaldor-Trevithick reflux mechanism cannot do the trick. Second, certain factors affecting the mechanism based on changes in relative interest rate differentials are identified that might preclude the mechanism from working as envisaged by its proponents. If this is the case, what we are left with is the concept of convenience lending.
Keywords: B50; E12; E51; 330; convenience lending; endogenous money; Post Keynesian economics; reconciliation problem